Penerapan Metode Seven Tools Terhadap Pengendalian Kualitas Telur Puyuh Pada UMKM Arkan Quail Farm - Bilqis, Bilqis; Nur Amallina, Davina Naswa; Yukabad, Marizka; Permata, Femi Aldilla; Al Qodariah, Nur Khansa; Manalu, Doni Sahat Tua; Wulandari, Andini (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2025)
The purpose of this study was to determine the types of defects in quail eggs, the level of defects in production, and the factors causing product defects in order to minimize the level of defects in the next production period using the Seven Tools method. This study was conducted on quail egg production by analyzing the types of defects in quail eggs and the factors causing them. In this study, the method used was the Seven Tools method, namely check sheet, histogram, pareto diagram, scatter diagram, fishbone diagram, and flowchart. In one month, 3369 quail eggs were defective. Based on the data obtained, there were four types of quail egg defects, including 674 soft shells, 1684 broken eggs, 337 cracked eggs, and 674 shells without patterns. In the application of quail egg quality control using the Seven Tools method, it was found that the largest type of defect occurred in broken quail eggs (50%). The factors causing the defective product based on the fishbone diagram include humans, methods, raw materials, and the environment